Diplomasi Budaya Indonesia melalui Kelas Gamelan di Korea Selatan pada Tahun 2021-2025 - Lestiono, Shafa Ramadhakhalisha; Yusuf, Talitha Raisa; Fitriyana, Dinda Ratu; Simatupang, Helga Yohana (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2025)
This study analyzes the implementation of gamelan classes as an instrument of Indonesian cultural diplomacy in South Korea during 2021–2025. Aker the Covid-19 pandemic, relations between Indonesia and South Korea strengthened, particularly through cultural and educational exchanges. The Indonesian Embassy in Seoul, in collaboration with the Seoul Institute of the Arts (SIA), revived gamelan classes as a medium of direct cultural engagement. Using a descriptive qualitative method, this research draws data from news articles, KBRI Seoul social media posts, and academic literature. Content analysis was employed to examine narratives, cultural representations, and communication strategies reflected in the program. The ﬁndings show that gamelan classes operate as an effective form of sok power, aligning with Nye’s concept of attraction and the cultural diplomacy frameworks of Melissen, Lenczowski, Patjinska, and Simon Mark. Beyond introducing traditional Indonesian music, the program promotes Indonesia’s image through values of harmony, collaboration, and cultural identity. Overall, this research highlights the relevance of participatory, learning-based cultural diplomacy in fostering closer relations between South Korean society and Indonesia and supporting long-term cooperation.